HIV-related knowledge, perceptions, attitudes, and utilisation of HIV counselling and testing: a venue-based intercept commuter population survey in the inner city of Johannesburg, South Africa - Chimoyi, L; Tshuma, N; Muloongo, K (My University, 2015)
Background: HIV counselling and testing (HCT) and knowledge about HIV have been key strategies utilised in the prevention and control of HIV/AIDS worldwide. HIV knowledge and uptake of HCT services in sub-Saharan Africa are still low. This study was conducted to determine factors associated with HCT and HIV/AIDS knowledge levels among a commuter population in Johannesburg, South Africa. Objective: To identify the factors associated with HCT uptake among the commuter population. Design: A simple random sampling method was used to select participants in a venue-based intercept survey at a taxi rank in the Johannesburg Central Business District. Data were collected using an electronic questionnaire. Logistic regression analysis assessed factors associated with HIV testing stratified by gender. Results: 1,146 respondents were interviewed, the ma[j]ority (n = 579, 50.5%) were females and (n = 780, 68.1%) were over 25 years of age. Overall HCT knowledge was high (n = 951, 83%) with more females utilising HCT facilities. There was a significant difference in HIV testing for respondents living closer to and further away from health facilities. Slightly more than half of the respondents indicated stigma as one of the barriers for testing (n = 594, 52%, p-value = 0.001). For males, living with a partner (aOR: 1.68, 95% CI: 1.02-2.78, p-value: 0.041) and possessing a post-primary education were positively associated with testing (aOR: 2.00, 95% CI: 1.15-3.47, p-value: 0.014), whereas stigma and discrimination reduced the likelihood of testing (aOR: 0.40, 95% CI: 0.31-0.62, p-value: <0.001). For females, having one sexual partner (aOR: 2.65, 95% CI: 1.19-5.90, p-value: 0.017) and a low perceived benefit for HIV testing (aOR: 0.54, 95% CI: 0.30-0.96, p-value: 0.035) were associated with HIV testing. Conclusion: The overall HIV/AIDS knowledge was generally high. Gender-specific health education and HIV intervention programmes are needed for improved access to HCT services. One favourable intervention would be the use of home-based HCT programmes.
PK
Keywords: HIV; South Africa